Performance Analysis of a Three-Stream Adaptive Cycle Engine during Throttling - Min Chen; Jiyuan Zhang; Hailong Tang (International Journal of Aerospace Engineering)
One advantage of the adaptive cycle engine (ACE) is its ability of throttling with constant airflow by the combined control of variable geometries, resulting in an improvement of spillage drag. However, the improvement is achieved at risk of a complex technical solution and control. This article investigates the selection scheme of variable geometries and engine configuration. It focuses on the performance of a three-stream ACE during throttling, whose configuration and control schedule are simpler than other types of ACEs. Five variable geometries are selected from seven available options through comparison analysis. The uninstalled thrust decreases from 100% to 60.36% during the subsonic throttling and to 59.81% during the supersonic throttling. Benefitting from the decreased spillage drag, the installed performance of the three-stream ACE is improved to some degree during throttling. This improvement is less than the result of a three-bypass ACE, whose configuration and control schedule are more complex. Thus, the three-stream ACE is a compromise design considering the technical risk and variable cycle characteristic, which is a better platform to verify the component technology and control schedule for the further research on a more complex type of ACE.